2001
DOI: 10.1038/35054069
|View full text |Cite
|
Sign up to set email alerts
|

Role for sperm in spatial patterning of the early mouse embryo

Abstract: Despite an apparent lack of determinants that specify cell fate, spatial patterning of the mouse embryo is evident early in development. The axis of the post-implantation egg cylinder can be traced back to organization of the pre-implantation blastocyst. This in turn reflects the organization of the cleavage-stage embryo and the animal-vegetal axis of the zygote. These findings suggest that the cleavage pattern of normal development may be involved in specifying the future embryonic axis; however, how and when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
140
6
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 233 publications
(163 citation statements)
references
References 12 publications
11
140
6
4
Order By: Relevance
“…1). These results are consistent with previous studies in ICSI-derived monkey embryos [38] and mouse embryos fertilized in vivo [19,36,39]. Most importantly, the presented data suggest that the relationship established between an egg and a sperm in early embryo development is not altered by the method of spermatozoon introduction.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…1). These results are consistent with previous studies in ICSI-derived monkey embryos [38] and mouse embryos fertilized in vivo [19,36,39]. Most importantly, the presented data suggest that the relationship established between an egg and a sperm in early embryo development is not altered by the method of spermatozoon introduction.…”
Section: Resultssupporting
confidence: 93%
“…In NM mouse eggs there is a reduced tendency to be penetrated by sperm near the animal pole, which is marked by the second polar body [13], whereas the most preferred place for sperm attachment is the equatorial region of the egg [19,36]. Our observations showed that both NM and IVF oocytes are most often approached by sperm at the equatorial site.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations